Burial mounds: glory of the living or monuments of the dead? - Potrebica, Hrvoje (2005)
Burial mounds are landmarks of mythological landscape, but they are also very important points of the physical landscape in which the settlement has more or less stressed central role. Their influence (both physical and mythological) is sometimes so great that they become the focal point of the space organization within the landscape. In this way monuments of the dead determine living space of the living. Analysis of spatial features of burial mounds which was the theme of similar session a few years ago suggested that spatial organization and position of burial mounds within the landscape is far more complex question than what was usually perceived as standard polis-necropolis relation. Necropolis is space where social structure of certain community creates its mythological and historical counterpart crucially important for claiming continuity and control over certain area through the process of adapting or accepting the physical landscape into their sacral and mythological landscape. Therefore, in order to gain control over the same area, any other community would have to erase or in some way adopt those landmarks. Secondary burials within or on burial mounds as well as construction of sanctuaries on such locations are reflection of religious structure that is imposing over the landscape, incorporating landmarks of their predecessors as their own. However, in this way living community also marks its control over certain area. The burial ritual imposes set of rules on the relationship between the living and the dead. Strict and detailed burial rite must have considerably involved the living community. The burial rites are supposed to establish the ritual bond between the living and the dead, and that makes the burial ritual one of the crucial bonding elements of any society based on strong concept of ancestors-descendants relationship. However, graves are not mere reflections of the world of living or of the social structure of their community. They are symbols and representations, pieces of symbolic language used by a certain community to communicate with its mythological component. In most cases, the elements of the grave inventory represent more the living community than the actual individual in the grave. This paper will also attempt to establish social value of such elements in construction of burial mounds and the Hallstatt burial ritual.
ENG